Growth and Productivity - Giancarlo Corsetti; John Flemming; Seppo Honkapohja; Willi Leibfritz; Gilles Saint-Paul; Hans-Werner Sinn; Xavier Vives (CESifo Forum, 2002)
This chapter compares growth in Europe and the United States in recent decades. Although Europe was, as one would expect, catching up in the 1950s and 1960s, this virtually ceased in the 1970s, and the United States has pulled further ahead in the 1980s and 1990s – and at a particularly remarkable rate in the second half of the last decade. The chapter examines the effects of general factor endowments and their accumulation with special emphasis on the role of information technology. Here the Scandinavian countries share a number of characteristics with the United States rather than the core European countries. The analysis highlights the effects of both industrial and labour market regulations in Europe as well as shortcomings in education and access to the Internet in much of the Continent. This last effect is attributed to inadequate openness of the sector to effective competition.
Keywords: 330